Herbal Medicine for the Treatment of Anorexia in Children: A Systematic Review and Meta-Analysis - Lee, Boram; Kwon, Chan-Young; Lee, Sun Haeng; Chang, Gyu Tae (Frontiers in Pharmacology, 2022)
Background: Anorexia is a common obstacle to adequate nutrition in childhood, a critical period for physical growth. East Asian traditional medicine treatment modalities including herbal medicine (HM) are considered an attractive therapeutic option, especially in East Asian countries. The purpose of this systematic review was to comprehensively examine the efficacy and safety of HM for anorexia in children. Methods: A total of 12 electronic databases from their inception date to June, 2021 were searched for randomized controlled trials (RCTs) assessing the efficacy of HM for the treatment of anorexia in children. The primary outcome was an improvement in anorexia clinical symptoms after treatment. In this meta-analysis, continuous and binary outcomes were assessed, and the data are presented as the mean difference or standardized mean difference and risk ratio (RR) with their 95% confidence intervals (CIs). The risk of bias and quality of evidence were assessed using the Cochrane Collaboration’s risk of bias tool and Grading of Recommendations, Assessment, Development, and Evaluations tool. Results: A total of 205 RCTs were included. A comparison of HM with placebo revealed that the total effective rate based on anorexia symptom improvement was significantly higher in the HM group (RR 1.58, 95% CI 1.34, 1.85). In comparison with controls, HM as monotherapy or adjunctive therapy to dietary supplements or conventional medications led to significant improvements in anorexia symptoms, body measurements, levels of blood biomarkers related to gastrointestinal function, and nutrition indices, with a lower recurrence rate of anorexia. No serious adverse events related to HM were reported. The risk of bias of the included studies was generally unclear, and the quality of evidence was generally low to moderate. Conclusion: Our study showed that HM could improve clinical symptoms, some anthropometric outcomes, and some biological markers related to appetite and growth in children with anorexia. However, considering the high risk of bias of the included studies and the heterogeneity of the HMs used, future research should focus on the use of standardized HMs and the implementation of methodologically robust clinical trials.